A Comparative Analysis of the Mechanism of Toll-Like Receptor-Disruption by TIR-Containing Protein C from Uropathogenic Escherichia coli - Anna Waldhuber; Greg A. Snyder; Franziska Römmler; Christine Cirl; Tina Müller; Tsan Sam Xiao; Catharina Svanborg; Thomas Miethke (Pathogens, 2016)
The TIR-containing protein C (TcpC) of uropathogenic Escherichia coli strains is a powerful virulence factor by impairing the signaling cascade of Toll-like receptors (TLRs). Several other bacterial pathogens like Salmonella, Yersinia, Staphylococcus aureus but also non-pathogens express similar proteins. We discuss here the pathogenic potential of TcpC and its interaction with TLRs and TLR-adapter proteins on the molecular level and compare its activity with the activity of other bacterial TIR-containing proteins. Finally, we analyze and compare the structure of bacterial TIR-domains with the TIR-domains of TLRs and TLR-adapters.